Trust, Authority, and Decision Making : Findings from the Extended Timor-Leste Survey of Living Standards - Dale, Pamela; Himelein, Kristen; Nikitin, Denis; Bexley, Angie (World Bank, Washington, DC, 2012)
This briefing note examines perspectives on trust, authority, and responsibility for decision making in Timor-Leste, using findings from the justice module included in an extension of the 2007 Timor-Leste Survey of Living Standards (TLSLS2) and a review of relevant social-science literature. It is hoped that this report will be a valuable resource for civil servants, civil society, and donor agencies working in Timor-Leste. This note examines relationships among East Timorese, focusing on trust, views on authority, and decision-making power. It begins by discussing the relationships between individuals specifically, trust in one's neighbors and perspectives on safety. While trust is essentially about these interpersonal relationships, research has shown that high levels of trust are associated with improved economic outcomes and better maintenance of public goods. Thus, trust within a society is important for a much wider set of outcomes. In later sections, the authors move to a discussion of individuals' relationships with institutions through the lens of community participation and beliefs about responsibility for dispute resolution. Throughout, the authors attempt to explain unusual findings or trends, making reference to relevant social-science literature. However, the authors also note where satisfying explanations have not been found, and welcome additional feedback and discussion on these areas.